Single-source precursor synthesis of gold (I) sulphide nanostructures for application in dye sensitized solar cells - Mposa, Esmie (My University, 2022)
The current study focused on synthesis of gold (I) sulphide nanostructures from a single-source precursor for use as a counter electrode (CE) in dye-sensitized solar cells (DSSCs). The single source precursor method was chosen as opposed to the usual dual source precursor synthesis method because there is safety in carrying out the synthesis procedures, ease of separation of nanocrystalline material and the use of lower decomposition temperatures. Gold dithiocarbamate complexes were synthesized using ethanol and dichloromethane as solvents for three hours. The complexes were characterized using Fourier transformer infrared spectroscopy (FTIR), nuclear magnetic resonance spectroscopy (NMR), single crystal X-ray diffraction (XRD), elemental analysis, ultraviolet-visible absorption spectroscopy, high resolution mass spectroscopy and thermogravimetric analysis. Upon complexation, there was a shift in the FTIR wavenumbers of the main functional groups from low to high frequencies. An up-field shift was observed in the NMR spectra of the complexes with respect to their relevant ligands. Single crystal XRD showed that the atomic packing of the complexes was orthorhombic with a space group of Fddd and triclinic with a space group P-1. All complexes decomposed within a temperature range of 200- 250 ℃ to form the Au2S nanostructures. The colloidal synthesis method was employed for the synthesis of the nanostructures because of its flexibility and ability to vary reaction parameters. As a result, the reaction time, temperature, precursor source and precursor concentration were varied to find the optimum conditions for the synthesis of the nanostructures. Au2S nanostructures were favoured with an average size of ~ 3 nm at a reaction temperature of 170 ℃ for 45 min in oleylamine, oleic acid and 1-octadecene with a precursor concentration of 3.837 M. Only three reaction parameters had an influence on the synthesized nanostructures; longer reaction times (60 min) resulted in larger nanoparticles due to Ostwald ripening, higher temperatures (200 ℃) also resulted in an increase in the nanostructures’ size and a mixed morphology was also observed due to the formation of elemental gold nanoparticles. A similar trend was also observed with precursor concentration, an increase in precursor concentration (7.674 M) resulted in an increase in the size of the synthesized nanostructures. The band gap energies of the nanostructures varied accordingly, the smaller the size of the nanostructures, the larger the band gap energy due to quantum confinement effects. The electrocatalytic activity of the Au2S nanostructures towards the reduction of the triiodide ions at the electrode/electrolyte interface was investigated in a three-electrode system and the results were compared to that of Pt under similar conditions. The Pt and Au2S had a peak current density of 1.45 mA and 1.20 mA, respectively and the minimal difference between the two suggests comparable catalytic activity of the Au2S CE. Consequently, DSSCs assembled with the Au2S reached a power conversion efficiency of 1.94% which was slightly lower but comparable to the conventional Pt CE 2.5%
A dissertation submitted in fulfilment of the requirements for the degree of Master of Science to the Faculty of Science, School of Chemistry, University of the Witwatersrand, Johannesburg, 2022